MARS OR VENUS? GENDER DIFFERENCES IN LANGUAGE LEARNING: A SOCIOLINGUISTIC STUDY ON LANGUAGE AND GENDER - Palancılar, Neziha (PEOPLE: International Journal of Social Sciences, 2017)
The question of how men and women learn and produce a foreign language differently has been a striking area to examine in the fields of Sociolinguistics and ESL. Foreign language teaching should aim at helping both genders acquire and improve skills to produce language effectively rather than merely concentrating on learning target grammar structures and vocabulary. Learning strategies used by male and female learners identify and shape the way they learn and acquire real-life skills. This paper addresses the differences in strategies used by male and female English language learners. The research question I will be discussing and elaborating on will be: How can we help learners succeed language learning process by considering gender differences and how can we raise awareness of these differences in language acquisition in order to plan and design courses to better meet learner needs and interests?In this project, I will be looking at the popular stereotypes and the Women’s Movement starting in the 1970s together with the Feminist Linguistic Activism to reveal and clarify more effective ways to help learners improve language skills. I will also present and discuss Sexism in educational materials and language practices to explore the commonalities across speech communities and to minimize the effects of the differences in language teaching.My research is an empirical research which concentrates on the classroom applications. I hope to help instructors choose non-sexist alternatives to increase the effectiveness of teaching both genders and assist them in designing more effective courses.